Electrical and material characterization of 0.24 micron CMOS device by using simulation / Nazirah Mohamat Kasim, Ahmad Puad Ismail Rosfariza Radzali - Mohamat Kasim, Nazirah; Ismail, Ahmad Puad; Radzali, Rosfariza (2009)
This project is to simulate and analyze the electrical characteristics for 0.24 micron CMOS device using SILVACO TCAD. The objective of the project is basically to simulate the fabrication process and electrical characterization for 0.24 micron CMOS devices. Electrical characteristics were carried out by using Atlas simulator while, simulation of the process is carried out by using Athena process simulator to modify theoretical values and obtain more accurate process parameters. At the device simulation process, the electrical parameter was extracted to investigate the device characteristics. Several design analysis are performed to investigate the effectiveness of the advanced method in order to prevent the varying of threshold voltage. The electrical characteristics produces the graph of drain current versus drain voltage, Id-Vd and drain current versus gate voltage, Id-Vg. From Id-Vg can be obtained the threshold voltage, VT where VT for NMOS transistor is lower than VT for PMOS transistor which is 0.6695V and -0.9683 V respectively. The gate length, Lg obtained from the simulated for NMOS and PMOS are same which is 0.235 micron and it is nearest to the scale for the project can be obtained.